DETERMINATION OF CORRELATION BETWEEN BIOFILM AND ESBL PRODUCERS OF ENTEROBACTERIACEAE - S.PRAMODHINI; S.UMADEVI (International Journal of Pharma and Bio Sciences, 2014)
Antibiotic resistance of bacteria in the biofilm mode of growth contributes to the chronicity of infections. This study was aimed to find out the prevalence of biofilm producers among the microorganisms isolated from our set up and to find out their antimicrobial susceptibility pattern with special reference to ESBL and AmpC producers. Total 169 clinical isolates were tested for biofilm production. Any bacterial species which showed resistance to any of third generation cephalosporin was tested for ESBL production and AmpC production. Among 169 isolates, 100(59.2%) were biofilm producers. In our study, 44(26%) and 43(25%) isolates were ESBL and AmpC producers respectively. Of 44 ESBL producers, 42(95.4%) and of 43 AmpC producers 39(90.7%) were biofilm producers.. Hence,clearing of biofilm would enhance the bacteria to respond to the therapy,to which it was refractory.